2005
DOI: 10.1289/ehp.7595
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Rates for Coronary Heart Disease in Relation to Residence Near Areas Contaminated with Persistent Organic Pollutants and Other Pollutants

Abstract: Exposure to environmental pollutants may contribute to the development of coronary heart disease (CHD). We determined the ZIP codes containing or abutting each of the approximately 900 hazardous waste sites in New York and identified the major contaminants in each. Three categories of ZIP codes were then distinguished: those containing or abutting sites contaminated with persistent organic pollutants (POPs), those containing only other types of wastes (“other waste”), and those not containing any identified ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 48 publications
(55 reference statements)
4
61
1
Order By: Relevance
“…A similar elevation in mortality from cardiovascular disease has been reported in occupational studies of dioxin-exposed workers (Flesch-Janys et al, 1995;Vena et al, 1998) and Seveso residents exposed to dioxin releases Pesatori et al, 1998). Sergeev and Carpenter (2005), examining rates of hospitalization for cardiovascular disease and acute myocardial infarction in residents living in zip codes containing or abutting hazardous waste sites contaminated with persistent organic pollutants, found statistically significant elevations of cardiovascular disease compared to populations not living near such waste sites. Hennig et al (2002) have demonstrated that dioxin-like PCBs induce oxidative damage of endothelial cells through the generation of reactive oxygen species (Slim et al, 1999).…”
Section: Discussionsupporting
confidence: 71%
“…A similar elevation in mortality from cardiovascular disease has been reported in occupational studies of dioxin-exposed workers (Flesch-Janys et al, 1995;Vena et al, 1998) and Seveso residents exposed to dioxin releases Pesatori et al, 1998). Sergeev and Carpenter (2005), examining rates of hospitalization for cardiovascular disease and acute myocardial infarction in residents living in zip codes containing or abutting hazardous waste sites contaminated with persistent organic pollutants, found statistically significant elevations of cardiovascular disease compared to populations not living near such waste sites. Hennig et al (2002) have demonstrated that dioxin-like PCBs induce oxidative damage of endothelial cells through the generation of reactive oxygen species (Slim et al, 1999).…”
Section: Discussionsupporting
confidence: 71%
“…Many epidemiologic studies have supported the notion that exposures to persistent organic pollutants (POPs) contribute to an increased risk of cardiovascular diseases. For example, persons having high concentrations of POPs such as polychlorinated biphenyls (PCBs) and 2,3,7,8-tetrachlorodibenzop-dioxin (TCDD) due to occupational or accidental exposures showed weakly or modestly elevated mortality due to cardiovascular events [12][13][14][15][16]. More recently, other studies have shown that residents living near areas contaminated with POPs had greater incidences of heart diseases and hypertension than those living in relatively clean areas [9,17].…”
Section: Discussionmentioning
confidence: 99%
“…Vietnam veterans who sprayed or handled Agent Orange, a herbicide containing dioxin, were found to have an increase in CHD morbidity [8,9]. In our previous studies, we observed a significant increase in the rates of hospitalization for atherosclerosis-related diseases (CHD, AMI, and stroke) in populations living in proximity to environmental sources of POPs [12,13]. In this study, we investigated the association between POPs and hospitalization rates for first-time AMI aggravated by comorbid DM for a reason.…”
Section: Discussionmentioning
confidence: 84%
“…Exposure to POPs is associated with an increased risk of atherosclerosis and its clinical manifestations (CHD, AMI, and cerebrovascular disease) in humans [7][8][9] and animals [10,11]. We have previously reported that environmental exposure to POPs, assessed by the residence near a POPs waste site, is associated with increased CHD and AMI hospitalization rates [12]. Shcherbatykh et al observed an increase in stroke hospitalization rates based on a similar exposure assessment [13].…”
mentioning
confidence: 89%